Reaction of rat connective tissue to mineral trioxide aggregate and diaket - Hammad Huda M; Abu-Zaghlan Maisoun S; Al-Omari Wael M (BMC, 2011)
Abstract Background The aim of this study was to compare the reaction of rat connective tissue to two root-end filling materials: white Mineral Trioxide Aggregate (WMTA) and Diaket. Methods Each of the materials was placed in dentine tubes and implanted subcutaneously in the dorsal connective tissue of 21 Wistar albino rats. Tissue biopsies were collected 7, 30, and 60 days after the implantation procedure. The specimens were processed and stained with hematoxylin and eosin and examined microscopically. After determining inflammatory cell numbers in sections from each specimen, inflammatory reaction scores were defined as follows: 0; no or few inflammatory cells (no reaction), 1; less than 25 cells (mild reaction), 2; 25 to 125 cells, (moderate reaction), and 3; 125 or more cells (severe reaction). Statistical analysis was performed using the Kruskal-Wallis and Mann-Whitney tests. Results There were statistically significant differences in the median inflammatory cell numbers throughout the three test periods, with the most severe degree of inflammation observed at the one-week period. Few cases of necrosis were observed with WMTA. Diaket exhibited the most severe degree of inflammation and necrosis. After 30 days, both materials provoked moderate inflammatory reaction. The eight-week period showed the least severe degree of inflammation in all groups. Conclusions It was concluded that WMTA exhibits a more favourable tissue response compared with Diaket which induced more severe inflammatory reaction than WMTA and the control.